Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2169/internalmedicine.4241-19
|View full text |Cite
|
Sign up to set email alerts
|

Alectinib-induced Immune Hemolytic Anemia in a Patient with Lung Adenocarcinoma

Abstract: Drug-induced immune hemolytic anemia (DIIHA) is a rare condition with an increasing incidence associated with the frequent use of certain drugs. An 85-year-old woman with lung adenocarcinoma prescribed alectinib complained of dyspnea on exertion at our hospital. Based on her laboratory tests results on admission, we focused on the clinical course of anemia and hemolysis progression after alectinib administration. The patient's anemia and hemolysis gradually improved after discontinuation of alectinib, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
(13 reference statements)
2
13
0
Order By: Relevance
“…Only one case of DIHA by alectinib from Japan has been reported. 8 Previous reports have not mentioned the dose of alectinib. The dosage of alectinib overseas is double the dosage used in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one case of DIHA by alectinib from Japan has been reported. 8 Previous reports have not mentioned the dose of alectinib. The dosage of alectinib overseas is double the dosage used in Japan.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 To our knowledge, only 7 references of DIHA caused by alectinib have been described. 8–14 In addition, there are potentially many other similar cases that have not been reported. However, no patient with grade 4 severe hemolytic anemia during treatment with alectinib has been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…In China, DIIHA has not yet been included in the medication risk monitoring system. It is now clear that there are nearly 140 drugs that can cause DIIHA through immune complex mechanisms (ie, drug-induced antibodies) [5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]38] , but DIIHA has not been included in the list of side effects of these drugs, and there is a lack of DIIHA vigilance, the vast majority of DIIHA may be missed, misdiagnosed, delayed in diagnosis, or given improper intervention, which increases the risk of patients' administration. Incorporating DIIHA into the medication risk monitoring system and improving the awareness and vigilance of DIIHA will help avoid the serious consequences of DIIHA on patients.…”
Section: Discussionmentioning
confidence: 99%
“…The NIPA mechanism can only cause a positive result of the direct antiglobulin test (DAT) and slow, di cult to observe slight hemolysis [6][7][8] . It has been reported that nearly 140 kinds of drugs can cause DIIHA through drug-induced antibodies, and there are 10 kinds of drugs with NIPA effect [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation